A reliability study of colour-Doppler sonography for the diagnosis of chronic cerebrospinal venous insufficiency shows low inter-rater agreement. Issue 11 (15th November 2013) - Leone, Maurizio A; Raymkulova, Olga; Lucenti, Ausiliatrice; Stecco, Alessandro; Bolamperti, Laura; Coppo, Lorenzo; Liboni, William; Rivadossi, Gianandrea; Zaccala, Giuseppe; Maggio, Maurizio; Melis, Fabio; Giaccone, Claudia; et al.
Abstract : Objective: Chronic cerebrospinal venous insufficiency (CCSVI) has been extremely variable, associated with multiple sclerosis in colour-Doppler sonographic studies. We aimed to evaluate inter-rater agreement in a colour-Doppler sonography venous examination. Design: Inter-rater agreement study. Setting: First-referral multiple sclerosis centre. Participants: 38 patients with multiple sclerosis and 55 age-matched (±5 years) controls. Intervention: Sonography was carried out in accordance with Zamboni's five criteria by eight sonographers with different expertise, blinded to the status of cases and controls. Each participant was evaluated by two operators. Primary and secondary outcome measures: Inter-rater agreement was measured through the κ statistics and the intraclass correlation coefficient. Results: The agreement was no higher than chance for criterion 2—reflux in the deep cerebral veins (κ=−0.02) and criterion 4—flow not Doppler detectable in one or both the internal jugular veins (IJVs) or vertebral veins (VVs; −0.09). It was substantially low for criterion 1—reflux in the IJVs and/or VVs (0.29), criterion 3—IJV stenosis or malformations (0.23) and criterion 5—absence of IJV diameter increase when passing from the sitting to the supine position (0.22). The κ value for CCSVI as a whole was 0.20 (95% confidence limit −0.01 to 0.42). Intraclass correlation coefficients for the measure of cross-sectional area ranged from 0.05 to 0.25. Inter-rater agreement was low for CCSVI experts (κ=0.24; −0.11 to 0.59) and non-experts (0.20; −0.33 to 0.73); neurologists (0.21; −0.06 to 0.47) and non-neurologists (0.18; −0.20 to 0.56); cases (0.19; −0.14 to 0.52) and controls (0.21; −0.08 to 0.49). Zamboni-trained neurosonographers ascertained CCSVI more frequently than the non-trained neurosonographers. Conclusions: Agreement was unsatisfactory for the diagnosis of CCSVI as a whole, for each of its five criteria and according to the different subgroups. Standardisation of the method is urgently needed prior to its further application in studies of patients with multiple sclerosis or other neurological diseases.